2000
DOI: 10.1093/jexbot/51.351.1721
|View full text |Cite
|
Sign up to set email alerts
|

Solute balance of a maize (Zea mays L.) source leaf as affected by salt treatment with special emphasis on phloem retranslocation and ion leaching

Abstract: Strategies for avoiding ion accumulation in leaves of plants grown at high concentration of NaCl (100 mol m(-3)) in the rooting media, i.e. retranslocation via the phloem and leaching from the leaf surface, were quantified for fully developed leaves of maize plants cultivated hydroponically with or without salt, and with or without sprinkling (to induce leaching). Phloem sap, apoplastic fluid, xylem sap, solutes from leaf and root tissues, and the leachate were analysed for carbohydrates, amino acids, malate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
8

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(101 citation statements)
references
References 59 publications
7
83
1
8
Order By: Relevance
“…Acid invertase is directly linked to sink strength, and any reduction in its activity will limit grain number in maize owing to accelerated kernel abortion (Hutsch et al 2014). However, salinity-induced reductions in assimilate translocation, from source to developing grains, are also responsible for poor grain setting and filling and ultimately grain yield (Lohaus et al 2000).…”
Section: Diminished Activities Ofmentioning
confidence: 99%
“…Acid invertase is directly linked to sink strength, and any reduction in its activity will limit grain number in maize owing to accelerated kernel abortion (Hutsch et al 2014). However, salinity-induced reductions in assimilate translocation, from source to developing grains, are also responsible for poor grain setting and filling and ultimately grain yield (Lohaus et al 2000).…”
Section: Diminished Activities Ofmentioning
confidence: 99%
“…Ammonium (NH4 + ) is usually undetectable [61 ] and nitrate (NO 3-) is found either at low concentration or undetectable [29,[61][62][63]. The uptake of sucrose and amino acids, and subsequently their concentration in phloem sap, is interdependent [64].…”
Section: Sugars and Amino Addsmentioning
confidence: 99%
“…The non-protein amino acid g-aminobutyric acid (GABA) is detectable in the sap of some species although a high level of GABA was suggested to be in some cases an artefact of the exudation technique [23]. Other organic components, such as polyamines, are also found in phloem sap [74], and organic acids, especially malic, succinic and citric acid, are normally present in a range of species [34,61,62].…”
Section: Sugars and Amino Addsmentioning
confidence: 99%
“…The data tabulated in Table 3 showed that Hyoscyamus species more accumulated Na (Okusnya and Ungar 1984) and Ca ++ (Lohaus et al 2000). Under drought conditions both D. innoxia and W. somnifera tended to accumulate more K + (5.67 meq/l than other species this may be to avoid sodium injury.…”
Section: Resultsmentioning
confidence: 98%